2013
DOI: 10.1186/1475-9276-12-54
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the relationships between social capital and socioeconomic inequalities in health: a contribution to understanding the psychosocial pathway of health inequalities

Abstract: IntroductionRecent research on health inequalities moves beyond illustrating the importance of psychosocial factors for health to a more in-depth study of the specific psychosocial pathways involved. Social capital is a concept that captures both a buffer function of the social environment on health, as well as potential negative effects arising from social inequality and exclusion. This systematic review assesses the current evidence, and identifies gaps in knowledge, on the associations and interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
286
3
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 312 publications
(344 citation statements)
references
References 54 publications
24
286
3
18
Order By: Relevance
“…It has previously been described that socio‐economic deprivation implies health inequalities for people with heart failure 19, 21. In addition, a review from 2013 states that people with lower socio‐economic status commonly have lower social capital than people with higher socio‐economic status,22 and low social capital was described as associated with inequalities in health 22. Thus, the present findings that showed that primarily people with lower income disagreed to the statements about received support and perceived they needed more support from different sources were in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been described that socio‐economic deprivation implies health inequalities for people with heart failure 19, 21. In addition, a review from 2013 states that people with lower socio‐economic status commonly have lower social capital than people with higher socio‐economic status,22 and low social capital was described as associated with inequalities in health 22. Thus, the present findings that showed that primarily people with lower income disagreed to the statements about received support and perceived they needed more support from different sources were in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different individuals can have different reasons for wanting or needing to get back to work. Social capital, such as social support from family and friends or managers and colleagues at work, can buffer some negative effects that lower socio‐economic status can have on health 22. Furthermore, to feel valued and appreciated can have major impact on people's self‐image and identity 25.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha señalado que a mayor capital social hay mejor salud y mejor autopercepción de salud, especialmente en personas con enfermedades crónicas. Para la oferta de servicios de salud preventivos y curativos, es importante tener en cuenta que en casos de menor capital social individual, el capital social comunitario ejercería un rol compensatorio y de reciprocidad entre las redes en la adaptación de las personas a los desafíos que provocan las enfermedades crónicas, especialmente en grupos socialmente vulnerables 19,20 . La confianza de las personas estaría más vinculada con la salud mental de la comunidad 14 .…”
Section: Discussionunclassified
“…La literatura indica, por una parte, que no existe consenso respecto al impacto del capital social de puente en la salud de las personas mayores y, por otra, que hay una débil reciprocidad entre mayor participación ciudadana con mejores oportunidades de acceso a los recursos institucionales y el cuidado individual de la salud 22,23 . En este estudio se encontró una correlación negativa significativa del arraigo territorial con el capital social total y sus componentes.…”
Section: Discussionunclassified
See 1 more Smart Citation